Critical chain project management - Leach, Lawrence P. (Artech House effective project management series., 2014)
Quick Start; Project Success; Defining the Problem; Project Management Body of Knowledge; Lean and Six Sigma; Project Management System; Project Solution; Starting a New Project; Developing the (Single-Project) Critical Chain Schedule; Developing the Multiproject Critical-Chain Plan; Execution; Project-Risk Management